d - 4 0 16; ational Commission on Culture and the Arts (Philippines). Committee on Literary Arts, publisher; 5 (Intramuros, Manila : National Commission for Culture and the Arts, National Committee on Literary Arts,2021)
u
Includes bibliographical references.
Keywords: 2 -- 0; 6; a; 20; 2